Frequency and Prognostic Impact of ALK Amplifications and Mutations in the European Neuroblastoma Study Group (SIOPEN) High-Risk Neuroblastoma Trial (HR-NBL1). Issue 30 (20th October 2021) - Bellini, Angela; Pötschger, Ulrike; Bernard, Virginie; Lapouble, Eve; Baulande, Sylvain; Ambros, Peter F.; Auger, Nathalie; Beiske, Klaus; Bernkopf, Marie; Betts, David R.; Bhalshankar, Jaydutt; Bown, Nick; et al.
Abstract : PURPOSE: In neuroblastoma (NB), the ALK receptor tyrosine kinase can be constitutively activated through activating point mutations or genomic amplification. We studied ALK genetic alterations in high-risk (HR) patients on the HR-NBL1/SIOPEN trial to determine their frequency, correlation with clinical parameters, and prognostic impact. MATERIALS AND METHODS: Diagnostic tumor samples were available from 1, 092 HR-NBL1/SIOPEN patients to determine ALK amplification status (n = 330), ALK mutational profile (n = 191), or both (n = 571). RESULTS: Genomic ALK amplification ( ALK a) was detected in 4.5% of cases (41 out of 901), all except one with MYCN amplification (MNA). ALK a was associated with a significantly poorer overall survival (OS) (5-year OS: ALK a [n = 41] 28% [95% CI, 15 to 42]; no- ALK a [n = 860] 51% [95% CI, 47 to 54], [ P < .001]), particularly in cases with metastatic disease. ALK mutations ( ALK m) were detected at a clonal level (> 20% mutated allele fraction) in 10% of cases (76 out of 762) and at a subclonal level (mutated allele fraction 0.1%-20%) in 3.9% of patients (30 out of 762), with a strong correlation between the presence of ALK m and MNA ( P < .001). Among 571 cases with known ALK a and ALK m status, a statistically significant difference in OS was observed between cases with ALK a or clonal ALK m versus subclonal ALK m or no ALK alterations (5-year OS: ALK a [n = 19], 26% [95% CI, 10 to 47], clonal ALK m [n = 65] 33% [95% CI, 21 to 44], subclonal ALK m (n = 22) 48% [95% CI, 26 to 67], and no alteration [n = 465], 51% [95% CI, 46 to 55], respectively; P = .001). Importantly, in a multivariate model, involvement of more than one metastatic compartment (hazard ratio [HR], 2.87; P < .001), ALK a (HR, 2.38; P = .004), and clonal ALKm (HR, 1.77; P = .001) were independent predictors of poor outcome. CONCLUSION: Genetic alterations of ALK (clonal mutations and amplifications) in HR-NB are independent predictors of poorer survival. These data provide a rationale for integration of ALK inhibitors in upfront treatment of HR-NB with ALK alterations.